Cochlear Meniere's: A Distinct Clinical Entity With Isolated Cochlear Hydrops on High-Resolution MRI? - Alonso, Jose E.; Ishiyama, Gail P.; Fujiwara, Rance J. T.; Pham, Nancy; Ledbetter, Luke; Ishiyama, Akira (Frontiers in Surgery, 2021)
Objective: Describe the clinical characteristics of patients with isolated cochlear endolymphatic hydrops (EH). Study design: Clinical case series Setting: Tertiary Neurotology referral clinic Patients: All subjects presenting to a University Neurotology clinic during a one-year period from July 2015 until August 2016 with isolated cochlear EH on MRI. Patients with a history of temporal bone surgery prior to the MRI were excluded. Intervention: High-resolution delayed-intravenous contrast MRI Main Outcome Measures: Audiometric and vestibular testing, clinical history analysis. Results: 10 subjects demonstrated isolated, unilateral cochlear hydrops on MRI. None of these patients met the criteria for Meniere’s disease. Mean age of the group was 66.4 years and most were males (70%). Unilateral aural fullness (70%), tinnitus (80%), and hearing loss (90%) were frequently observed. Only one patient presented with disequilibrium (10%) and one patient had a single isolated spell of positional vertigo one month prior to the MRI (10%) but no further vertigo spells in the 4 years following the MRI. Mean PTA was 37.8 dB which was significantly decreased from the non-affected ear with PTA of 17.9 (p<0.001). One patient developed vertiginous spells and disequilibrium 4 years after initial presentation and a repeat MRI revealed progression to utricular, saccular and cochlear hydrops. Vestibular testing was obtained in five patients with one patient presenting with 50% caloric paresis and all others normal. Acetazolamide was tried in 7 patients with 86% reporting subjective clinical improvement. Two out of the ten patients had a history of migraine (20%). Conclusions: Patients with MRI exhibiting isolated cochlear EH present with predominantly auditory symptoms: mild to moderate low-frequency hearing loss, aural fullness, tinnitus without significant vertigo. Isolated cochlear hydrops is more common in males, average age in mid-60s and there is a low comorbidity of migraine headaches. This contrasts significantly with patients with isolated saccular hydrops on MRI from our prior studies. We believe that isolated cochlear EH is associated with a specific clinical phenotype that is distinct from Meniere’s disease or its variant delayed endolymphatic hydrops and we propose that cochlear Meniere’s disease should be reconsidered as a separate and distinct entity from Meniere’s disease.